Stage-specific distribution of oxidative radicals and antioxidant enzymes in the midgut of Leptinotarsa decemlineata - Krishnan, Natraj; Kodrík, Dalibor; Turanli, Ferit; Sehnal, Frantisek (Journal of insect physiology, 2007)
The titers of reactive oxygen species (ROS) represented by superoxide anion and general peroxides, and the activities of antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT), are regulated in the midgut of the Colorado potato beetle (CPB) relative to the gut compartment, developmental stage, and food intake. ROS concentration is low in the potato leaves but it is very high in their digest in insect's anterior midgut. It is proposed that intensive ROS production in this gut region is linked to the processing of allelochemicals. SOD and CAT activities, low oxygen tension, and unidentified redox systems that maintain a slightly reducing milieu in the midgut lumen (pe+pH=6.95 declining to 5.36), obviously contribute to the decrease of ROS concentration along the gut length to a minimum in the wall of posterior midgut region. SOD and CAT activities are higher in the potato leaves than in the midgut tissues but the role of plant enzymes in ROS elimination within the gut lumen remains to be shown. A lower level of ROS and a higher antioxidant potential in the adult than in the larval midgut indicate stage specificity in the management of oxidative stress. The antioxidant defense is high in the diapausing adults that contain no detectable superoxide and about ten times less peroxides than the reproducing adults.
Keywords: brouci; listy rostlin; antioxidancia; reaktivní formy kyslíku; Gastrointestinal Tract; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; Reactive Oxygen Species; larva; Animals; Antioxidants; Gastrointestinal Motility; zvířata; Plant Leaves; Coleoptera; gastrointestinální trakt; gastrointestinální motilita; Larva; Solanum tuberosum